Fake News and Internet Shutdowns in Indonesia: Symptoms of Failure to Uphold Democracy - Rofi Aulia Rahman; Shu-Mei Tang (Constitutional Review, 2022)
The Indonesian government limited or shut down internet access during separate riots in Jakarta and Papua in 2019. The justification for blocking the internet and disabling certain features of social media platforms was to quell the unrest by ceasing the spread of fake news. Nevertheless, the government did not declare a state of emergency in response to either situation, triggering debate on whether the internet restrictions had any strong constitutional basis or if they were out of proportion and unconstitutional. This study evaluates the government’s policy on internet shutdowns to reduce the spread of fake news amid riots, and explicates when the state of emergency “feature” might be activated. The research method of this article is a doctrinal legal approach, which critically examines whether the government policy was excessive, and to what extent a state of emergency can be implemented by minimum standard requirements. The result of this study shows the riots in Jakarta and Papua ought not be categorized as national threats; hence, the internet shutdown was out of proportion. Fake news is part of the price we pay for a free society; thus the article argues that an internet shutdown is not a proper way to combat fakenews. Furthermore, the government has failed to fulfill the minimum standards to justify the internet shutdowns. Access to the internet is a new face of democratic pillars, so blocking internet access without any sufficient legal instruments and correct constitutional interpretation might indicate symptoms of a failure to uphold democracy.